Molecular factors governing perineural invasion in malignancy. (June 2022) - Ahmadi, Navid; Kelly, Gretel; Low, Tsu-Hui (Hubert); Clark, Jonathan; Gupta, Ruta
Abstract: Background: Perinueral invasion (PNI) is recognized as an independent adverse prognostic factor associated with shorter disease free and disease specific survival in a range of malignancies. However, not all histologically detected PNI demonstrate aggressive biologic behaviour. Herein, we systematically review the literature to identify neurotrophic biomarkers that may potentially be used to predict the biologic potential of PNI. Method: A systematic review was conducted based on PRISMA guidelines utilising the search terms 'PNI', 'DNA' and 'RNA' analysis in select malignancies following registry of the search strategy on PROSPERO. The biologic role of the molecular markers identified through the literature review was examined using publicly available databases, such as Gene Cards and Kyoto Encyclopedia of Genes and Genomes (KEGG) with a focused literature review of the identified pathways. Results: The systematic search identified 256 studies, of which 78 studies were suitable for data extraction. A variety of methodologies including immunohistochemistry, immunoblotting, nucleic acid sequencing, Luciferase assays and CRISPR techniques have been undertaken to evaluate the biologic potential of PNI. The studies evaluated 136 unique molecules. Of these, only 15 molecules were investigated through multiple studies with concordant results or had robust functional analyses. Three pathways were identified as playing a role in PNI, namely; the epithelial-mesenchymal transition pathway, neurotrophic pathway and Notch pathway. Discussion: Our understanding of the complex and reciprocal interaction between tumour and nerve cells that drives PNI is still evolving. The knowledge gaps can largely be attributed to publication bias, lack of availability of high-quality patient derived tissues and limitations of currently available technology. This review summarises the current knowledge regarding development and progression of PNI that can be harnessed for prognostication and treatment. This review also summarises the lacunae in our understanding of the pathogenesis of PNI thus identifying avenues for future studies. Highlights: Systematic review of 256 studies evaluating 135 molecules and their relationship with PNI in 7 malignancies from 19 countries. 15 molecules were identified, with either concordant results or robust functional analyses, that identified 3 pathways involved in PNI. EMT, neurotrophic and Notch pathway were explored through literature and publicly available databases to establish likely mechanism of contribution to PNI. Current evidence for biomarkers of PNI within these 3 pathways were explored and future direction for research is suggested.